2021
DOI: 10.3390/cancers13040707
|View full text |Cite
|
Sign up to set email alerts
|

The Vault Nanoparticle: A Gigantic Ribonucleoprotein Assembly Involved in Diverse Physiological and Pathological Phenomena and an Ideal Nanovector for Drug Delivery and Therapy

Abstract: The vault nanoparticle is a eukaryotic ribonucleoprotein complex consisting of 78 individual 97 kDa-“major vault protein” (MVP) molecules that form two symmetrical, cup-shaped, hollow halves. It has a huge size (72.5 × 41 × 41 nm) and an internal cavity, wherein the vault poly(ADP-ribose) polymerase (vPARP), telomerase-associated protein-1 (TEP1), and some small untranslated RNAs are accommodated. Plenty of literature reports on the biological role(s) of this nanocomplex, as well as its involvement in diseases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 218 publications
(393 reference statements)
0
27
0
1
Order By: Relevance
“…There are also a few studies connecting the vault complex to drug resistance [ 28 , 51 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 ], although it is still under dispute since reliable changes of drug resistance were not observed in in vivo experiments using MVP KO mice [ 26 , 123 , 124 ]. In addition to nuclear-cytoplasmic transport and drug resistance, it was reported that the vault complex participates in intracellular signaling pathways, DNA damage repair and anti-apoptotic processes, most of which are closely related to cancer [ 50 , 125 , 126 , 127 , 128 , 129 ].…”
Section: Mvp and The Vault Complex: Implications To Cell Proliferatio...mentioning
confidence: 99%
“…There are also a few studies connecting the vault complex to drug resistance [ 28 , 51 , 115 , 116 , 117 , 118 , 119 , 120 , 121 , 122 ], although it is still under dispute since reliable changes of drug resistance were not observed in in vivo experiments using MVP KO mice [ 26 , 123 , 124 ]. In addition to nuclear-cytoplasmic transport and drug resistance, it was reported that the vault complex participates in intracellular signaling pathways, DNA damage repair and anti-apoptotic processes, most of which are closely related to cancer [ 50 , 125 , 126 , 127 , 128 , 129 ].…”
Section: Mvp and The Vault Complex: Implications To Cell Proliferatio...mentioning
confidence: 99%
“…Vault ribonucleoproteins are large hollow barrel-like shape particles in the cytoplasm of many eukaryotic cells. Although little is known yet on their function, they have been involved in key regulatory roles including autophagy, apoptosis and modulation of gene expression [reviewed by Frascotti et al, (2021)]. Even more, recent evidence has shown that human vtRNA1-1 could guide sequence-specific cleavage of a complementary target RNA (Frascotti et al, 2021).…”
Section: Vtrnas Are Enriched In the Secreted Fractionmentioning
confidence: 99%
“…Vault particles, large, hollow ribonucleoprotein cages, have been investigated as drug delivery vehicles. Their roles in several mechanisms and pathways have been studied and they are emerging as potential delivery vehicles for therapeutic molecules [83][84][85][86]. However, they have not been widely studied for vaccine development.…”
Section: Outstanding Questionsmentioning
confidence: 99%